Polyphenolics, glucosinolates and isothiocyanates profiling of aerial parts of Nasturtium officinale (Watercress) - Kyriakou, Sotiris; Michailidou, Kyriaki; Amery, Tom; Stewart, Kyle; Winyard, Paul G.; Trafalis, Dimitrios T.; Franco, Rodrigo; Pappa, Aglaia; Panayiotidis, Mihalis I. (Frontiers in Plant Science, 2022)
Watercress (Nasturtium officinale) is a rich source of secondary metabolites with disease-preventing and/or health-promoting properties. Herein, we have utilized extraction procedures to isolate fractions of polyphenols, glucosinolates and isothiocyanates to determine their identification and quantification. In doing so, we have utilized reproducible analytical methodologies based on liquid chromatography with tandem mass spectrometry by either positive or negative ion mode. Due to the instability and volatility of isothiocyanates, we followed an ammonia derivatization protocol which converts them into respective ionizable thiourea derivatives. The analytes’ content distribution map was created on watercress flowers, leaves and stems. We have demonstrated that watercress contains significantly higher levels of gluconasturtiin, phenethyl isothiocyanate, quercetin-3-O-rutinoside and isorhamnetin, among others, with their content decreasing from flowers to leaves to stems. Pearson’s correlation analysis has shown that the content of isothiocyanates doesn’t depend only on the bioconversion of individual glucosinolates but also on other glucosinolates of the same group. Overall, we have provided comprehensive analytical data of the major watercress metabolites thereby providing an opportunity to exploit different parts of watercress towards potential therapeutic applications.